Decision of Student's Dormitory Accommodation Using SAW Method - Muhammad Fahrurrozi; Arita Witanti (International Journal of Informatics Engineering and Computing, 2024)
This study presents the development and evaluation of a Decision Support System (DSS) designed to streamline the student selection process for dormitory administrators. The system leverages the Simple Additive Weighting (SAW) method to evaluate applicants based on predefined criteria, including academic performance, financial need, and extracurricular involvement. Testing conducted on five applicants demonstrated a 100% accuracy rate, validating the system's effectiveness in identifying the most suitable candidates. The SAW method's ability to aggregate and normalize multiple criteria into a single quantitative score ensures a robust, transparent, and fair decision-making framework. This approach significantly enhances the precision of candidate selection while reducing manual effort and minimizing biases. The system's adaptability allows for the incorporation of additional criteria or adjustments to weighting schemes, ensuring its applicability across diverse institutional contexts. The successful implementation of this system underscores the value of integrating multi-criteria decision-making techniques into administrative workflows, offering a scalable and accountable solution for optimizing resource allocation in dormitory management.